Longevity of Anterior Composite Restorations for Localized Tooth Wear: A Scoping Review - Sindhu Rajarajan; Neil Nathwani; Touraj Nejatian; Peter Fine; Albert Leung (MDPI AG, 2023)
(1) Objective: This scoping review evaluates composite restorations as a treatment modality for anterior tooth surface loss and investigates the longevity of the direct and indirect composites used herein. (2) Method: The search encompassed Medline, Embase, Web of Science, the Cochrane Library, and hand search utilizing the PICO framework. (3) Results: Eight studies were included in this review, comprising one randomized controlled trial, one retrospective, and six prospective studies. Some studies reported favorable outcomes for composite restorations in anterior teeth. Although not statistically significant, evidence supported the anterior composite as a viable short- to medium-term solution for managing tooth wear. Direct resin composites were deemed clinically and cost-effective when managing localized anterior tooth wear. However, limitations and inconsistencies in this scoping review limited definitive clinical recommendations. (4) Conclusions: Further research, including well-managed randomized controlled trials using standardized protocols and longer follow-up periods, is essential to reconfirm the long-term efficacies of anterior composite restorations when managing tooth wear. A robust research design and exacting protocols could facilitate more meaningful clinical conclusions.